Pelatihan Dasar Entrepreneuship Di Era Digital Kepada Siswa-Siswi SMAK Yos Sudarso Kota Batam - Mohamman Thamdzir; Siska Amelia Maldin; Taufik Bachrul Ulum Lubis (JURNAL KEKER WISATA, 2023)
High unemployment and limited job vacancies in Indonesia force us all to become entrepreneurs, but limited knowledge, skills and motivation are the main obstacles. The millennial generation as the future young generation of the Indonesian nation needs to be trained and have their competencies increased so that the technology they consume can be useful and generate income for themselves or others. The purpose of this digital entrepreneurship training is as entrepreneurship education based on technology that is already attached to them, which is one of the important and strategic aspects to increase competitiveness and reduce unemployment which has an impact on Indonesia's economic stability. Entrepreneurship training seeks to create a mental attitude and spirit that is always active or creative, empowered, creative, creative and modest and trying to increase income in its business activities. Entrepreneurship needs to be instilled and developed since he was young, since he was still in school. The emergence of the current problem is the large number of unemployed and the difficulty of getting a job, so the expected results with entrepreneurial knowledge obtained from digital entrepreneurship training will be the capital later to open their own business from a young age. The results were already visible from their enthusiastic attitude in participating in this training and even some of the participants were able to create a business website, register on the market place and dare to promote their products on social media.